Restorative Justice Institutions Model for Resolving Problems and Conflicts in Mining Businesses and Environmental Management - Ilyas; Ichsan, Nursyamsi; Nasir, Citras; Hasmiati Attas, Nasrah; Saputra, Tri Eka (Journal of Indonesian Scholars for Social Research, 2022)
Justice for resolving problems and conflicts in mining businesses and environmental management (LH) in Makkuaseng Village, Batu Putih District, North Kolaka Regency. Research analysis method using qualitative techniques. As a result, the development of the Restorative Justice (RJ) model in resolving conflicts and legal problems in the mining and environmental sectors: First, community members seeking justice have a choice in resolving a problem they face, namely being able to submit a report of their legal problem first to law enforcement (Police). ), law enforcement as facilitators can bring the problem to the Restorative Justice Institute (LRJ) for a solution. Second, report the legal problems faced to LRJ for resolution. Third, the problem-solving process at LRJ is carried out through specific mechanisms and stages, which are based on the principle of deliberation and consensus. Fourth, problem resolution at LRJ ends with a binding decision for the parties to the dispute, the perpetrator and the victim.